A Mechanical Coil Insertion System for Endovascular Coil Embolization of Intracranial Aneurysms - Haraguchi, K. (Centauro S.r.l., 2013)
Like other fields of medicine, robotics and mechanization might be introduced into endovascular coil embolization of intracranial aneurysms for effective treatment. We have already reported that coil insertion force could be smaller and more stable when the coil delivery wire is driven mechanically at a constant speed. Another background is the difficulty in synchronizing operators' minds and hands when two operators control the microcatheter and the coil respectively. We have therefore developed a mechanical coil insertion system enabling a single operator to insert coils at a fixed speed while controlling the microcatheter. Using our new system, the operator manipulated the microcatheter with both hands and drove the coil using foot switches simultaneously. A delivery wire force sensor previously reported was used concurrently, allowing the operator to detect excessive stress on the wire. In vitro coil embolization was performed using three methods: simple mechanical advance of the coil; simple mechanical advance of the coil with microcatheter control; and driving (forward and backward) of the coil using foot switches in addition to microcatheter control. The system worked without any problems, and did not interfere with any procedures. In experimental coil embolization, delivery wire control using the foot switches as well as microcatheter manipulation helped to achieve successful insertion of coils. This system could offer the possibility of developing safer and more efficient coil embolization. Although we aim at total mechanization and automation of procedures in the future, microcatheter manipulation and synchronized delivery wire control are still indispensable using this system.